Enhancement of Fibrinolysis by Plactins: Structure-activity Relationship and Effects in Human U937 Cells and in Mice - Inoue, Toshiki; Hasumi, Keiji; Sugimoto, Maki; Endo, Akira (Thrombosis and Haemostasis, 1998)
Plactin D, a cyclic pentapeptide [cyclo(-D-Val-L-Leu-D-Leu-LPhe-D-Arg-)] produced by a fungal strain, enhances fibrinolytic activity (6). The present study deals with the structure-activity relationship of plactins and their effects in U937 cells and mice. The results obtained from 50 plactin D analogues with a single amino acid substitution demonstrated that the following substitutions were detrimental: the enantiomer for each of the five residues; a polar, an acidic or a basic residue for D-Val, L-Leu, D-Leu or L-Phe; a polar, a hydrophobic or an acidic residue for D-Arg. On the other hand, a compound with L-Leu or L-Val in place of L-Phe was seven times as active as plactin D. These results suggest an essential role of a sterically restricted arrangement of four hydrophobic residues and the adjacent basic residue. The enhancement of fibrinolysis was dependent on plasma, ranging from 2- to 3-fold when U937 cells were incubated with 15-30 μM plactin D in the presence of 6-50% plasma, while no elevation was observed when cells were incubated in the absence of plasma. Plasminogen alone could not substitute for plasma. The plactin D effect was totally abolished by anti-urokinase IgG but not by anti-tissue plasminogen activator IgG. Plactin D caused a plasma-dependent, transient increase in the cellular urokinase activity. This urokinase activation may have accounted for the increased fibrinolytic activity of plactin D-treated U937 cells. Homogenates of the lung obtained from mice 0.5 to 2 h after intravenous plactin D (5 mg/kg) showed 2- to 3-fold increased levels of fibrinolytic activity, while activities of the brain, heart, liver, spleen, kidney and aorta were not significantly affected. In conclusion, plactin D enhances fibrinolysis both in cultured mammalian cells and in experimental animals.